Николай Адонц (1871-1942) - Ферешетян, Вардан (Зангак-97)
Nikolay Adonts is not only a historian but as well a “chronicler” in the exact classical meaning of the word. He knew the simple truth that without the harmonious combination of the higher cognition and the deepest sensuality one cannot write the history, which has been the peculiar distinction of our medieval chroniclers and which is seemingly being neglected by many of our contemporary historians. In his work “The Ancient Armenian World Outlook” Adonts for the fist time tries to reveal the bases, the parallels and interpenetrations of our mythical Weltanschauung. In the treatise “The Art Grammar of Dionysius and His Armenian Interpretations” through textographical philological comparison of the manuscript variants Adonts recreated the interpretations of David Philosopher, the Anonymous Interpreter, Movses Kertogh, Stepanos Syunikian, Gregory Magistros, Amam of the East. Systemizing by chapters and fragments the grammatical contemplations of David Philosopher and Greek grammaticists he has studied a number of significant questions of the Greek school. Constantly highlighting the role of reasoning, reflecting and the task of forming a holistic and dynamic Weltanschauung, while understanding at the same time that the history is not only a mere sequence of actions but as well and in the first place the reflection of perception and comprehension, Nikolay Adonts has written: “The individual either alone or in community acts in as much as his comprehension goes. One can state with confidence that the level of maturity of a nation, the horizons of its vision, are very often determining as well the path of its history…”
Keywords: Биография